Determination of the bio-economical efficiency of milk production throughout data envelopment analysis models - Cobo, Ra?l; Borroto, Omelio (Cuban Journal of Agricultural Science, 2013)
In order to demonstrate the potentialities of the data envelopment analysis (DEA) and its value for interpreting milk production, the efficiency frontier of the selected Basic Units of Cooperative Production (BUCP) is presented. The application of the econometric tools to interpret the results easier and take decisions and show an effective comparison in efficiency terms whether for the use of resources or maximization of results is presented. For developing this research, the techniques of the data envelopment analysis (DEA) were used and the weight assignment of the variables through the statistical model of impact measuring (SMIM) was corrected. The SPSS V.19.0 (2010) software was used for the data processing according to the SMIM and the Frontier Analyst to conduct the DEA. Besides, calculation sheets from Excel were used to form the matrix of original data. The information of six BUCP between January 2008 and August 2010 was used, gathering information monthly. The variables explaining higher percentage in the system variability were known, and the technical efficiency and the efficiency frontier according to the variables selected were determined. Key words: efficiency, econometry, milk production, data envelopment analysis.